Types of non-normative legal acts of the Republic of Azerbaijan - Turabova, Sumbul Faig gizi (Теоретичні питання юриспруденції і проблеми правозастосування: виклики ХХІ століття : тези доп. учасників X Міжнар. наук.-практ. конф. (Харків, 25 трав. 2025 р.), 2025)
It is noted in the article that the Republic of Azerbaijan, having officially enshrined in its constitutional legislation the concept of “acts of a normative nature”, allowed the operation of mixed legal acts along with normative legal acts and individual legal acts. Thus, through the adoption of acts of a normative nature and non-normative legal acts, the implementation of general legal provisions in various areas of national law is ensured. In the article, it is especially noted that the procedure for adopting non-normative legal acts is significantly different from the norm-making process. It is quite simple and not regulated in detail. Nevertheless, the peculiarities of the adoption of some non-normative legal acts are reflected in the current legislation.